Being Alive, Living a Life. The Unity of the Concept of Life in Pseudo-Dionysius the Areopagite - Stępień, Tomasz (Verbum Vitae, 2021)
The writings of Corpus Dionysiacum present a concept of life which is different from the one that we profess nowadays. Its view is backed up mainly by the Platonic tradition, which since the times of Plato has tended to see life as an intellectual principle. Therefore, in the Neoplatonic system we can find the conviction that life, in its fullest sense, is intellectual and at its peak is a vision of the One. In the system of Proclus, life, apart from being a principle, is also a god and the main principle of the whole world of intellectual and intellective gods. Pseudo-Dionysius in his writings exploits the concept of the unparticipable and participable principle, and since God is for him Trinity completely beyond participation and knowledge, the divine names play the role of participable henads. However, for Dionysius, names are neither hypostases nor living gods, which is clearly visible in case of the name of Life. All things participate in the name of life and in this name God is the only principle of life in the universe. However, life is not a property to own, but rather a constant struggle to approach the Trinity. Therefore, by committing a sin, an angel or a man loses life, which in the case of a man can be regained through sacramental activity. An analysis of the thoughts of Pseudo-Dionysius reveals a conception of life which is unified contrary to its shattered modern understanding. While biological, mental, moral lives fundamentally differ for us, for Dionysius those are merely aspects of the same thing, and therefore in his view life can be lost and regained not only in the metaphorical, but also the ontological sense.